The effects of high-velocity hamstring muscle training on injury prevention in football players - Kamandulis, S.; Cadefau, J. A.; Snieckus, A.; Mickevicius, M.; Lukonaitiene, I.; Muanjai, P.; Satkunskiene, D.; Molina, V.; de Blas Foix, X.; Conte, D. (Frontiers in Physiology, 2023)
Background: Explosive and fast body movements, sprints, jumps and quick changes of direction, which are characteristic of the football training, place considerable strain on the hamstring muscles. Due to the high occurrence of hamstring injuries, new preventive strategies are required that focus on high-velocity training. The purpose was to assess the effectiveness of high-velocity elastic-band training in reducing the occurrence of hamstring injuries in football players.